Identification of Ergonomic Risk on Workers Using Quick Exposure Check and Rapid Upper Limb Assessment Methods - Erliana, Cut Ita; Irwansyah, Defi; Abdullah, Dahlan; Zega, Subhansah; Hasibuan, Muammar Faturrahman (STMIK Dharma Wacana, 2022)
Pulau Tiga Palm Oil Mill (PKS) is one of the business units of PT. Nusantara I Plantation located in Pulau Tiga Village, Tamiang Hulu District, Aceh Tamiang Regency, is engaged in palm oil processing. Some workstations at PKS Pulau Tiga still use a manual work system, then the factor of long working hours, which is 12 hours of work/day, can make it easier for workers to experience fatigue and result in musculoskeletal complaints for workers. The purpose of this study is to identify which workstations are most at risk and which workstation facilities must be improved. The methods used in this study are the QEC, NBM, and RULA Methods.